The Social Portrait of Latvian Anti-Soviet Armed Resistance in the Beginning of German-Soviet War in Summer 1941 - Jānis Tomaševskis (Latvijas Universitātes Žurnāls. Vēsture)
So far, historiography has focused only on the causes and military aspects of the Latvian anti-Soviet armed resistance in 1941. The quantitative and qualitative data presented in a survey conducted by the Latvian Statistical Bureau in 1941–1942 enable analysing the social portrait of the resistance fighters. The research has yielded the conclusion that the social portrait of the resistance fighters manifested essential differences in ethnic composition and religious affiliation compared to the social portrait of Latvia’s population in the pre-war period. On the other hand, it corresponded to the social portrait of the counties of Latvia that were home to the majority of the resistance members. Proportion of married persons among the resistance fighters was at least by 22.5% higher than the average indicator in the pre-war period, that probably indicates of higher motivation to resist the Soviet rule among family men.